Perceived Social Support and Subjective Well-being of Ex-service People of the Indonesian Defence Forces - Setiasih Setiasih; I Gusti Ayu Putu Mas Jayanti (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Retired people often feel unhappy (have low subjective well-being – SWB). Perceived social support is a form of stress buffer, which can play the role of an additional resource, for an individual facing the challenges of life (as a pensioner). The goal of this study is to ascertain the connections between perceived social support and SWB for ex-servicemen and women of the TNI. The retired TNI subjects (N = 40) live in Denpasar (Bali). Data collection was conducted using the Interpersonal Support Evaluation List, the Satisfaction with Life Scale, and the Positive and Negative Effects Scale. Data analysis used the correlation technique of Pearson and Spearman. The results showed a significant positive correlation between perceived social support and life satisfaction (r = .420; p(.007) < 0.05) and a positive effect (r = .667; p(.000) < 0.05). There was no significant negative correlation shown between perceived social support and negative effects (r = - .208; p(.119) > 0.05).